An Empirical Analysis of Popular Press Claims Regarding Linguistic Change in President Donald J. Trump - Coutanche, Marc N.; Paulus, John P. (Frontiers in Psychology, 2018)
Linguistic features of a person’s speech can change over time. It has been proposed that characteristics in the speech of President Donald J. Trump (DJT) have changed across time, though this claim has been based on subjective and anecdotal reports. A previous study of speech by Presidents of the United States identified an increase in the use of conversational fillers and non-specific nouns, and lower unique word counts, in the speech of President Ronald W. Reagan over seven years, but not in the speech of President George H.W. Bush. To empirically test claims of a systematic change in speech by DJT, we applied the same analysis by transcribing and analyzing publicly available Fox News interviews with DJT between 2011 and 2017. A regression analysis revealed a significant increase in the use of filler words by DJT over time. There was no significant change in numbers of unique words. The observed rise in filler words was significantly greater than filler-word change in President George H.W. Bush, and was not significantly different from the rise previously found in the speech of President Reagan. Identifying the reason for this linguistic change is not possible from speech samples alone, and the variables index linguistic change rather than being validated measures of change in cognitive ability. Nonetheless, features of the data such as the trajectory starting years before announcement of candidacy rule-out several potential explanations. To summarize, we find statistical evidence to support suggestions that speech by DJT has changed over time.